Positive electrode material precursor and preparation method thereof, positive electrode material, and secondary battery

During the preparation process of the co-precipitation method of the ternary positive electrode material precursor, an annular doping layer arranged in the circumferential direction is formed, the problem of low lithium ion transmission efficiency is solved, the electrochemical performance is improved and cost control is achieved, and the process stability is ensured.

CN119735246APending Publication Date: 2025-04-01YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954875.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the improvement of the electrochemical performance of ternary positive electrode materials, how to improve lithium ion transmission efficiency while ensuring cost control and process stability, and avoid material structure changes and environmental pollution risks caused by excessive or improper doping.

Method used

The positive electrode material precursor is prepared by co-precipitation method. The core is formed by continuously passing the oxidant in the early stage of the co-precipitation reaction, and then the pH in the reactor is lowered to allow the particles to continue to grow. When the particle size reaches 40%-80%, the oxidant is reduced or stopped. The dopant solution is pumped under the protection of inert gas to form an annular doping layer arranged in the circumferential direction, ensuring that the doping elements grow at a specific position, forming a transition zone similar to the annular shape, and unblocking the lithium ion transport channel.

Benefits of technology

It improves the electrochemical performance of ternary materials, especially capacity characteristics, reduces the blockage caused by the mixed discharge of lithium ions and nickel ions, increases the lattice spacing, makes lithium ions migration smoother, achieves improvement in material performance, and controls raw material cost and process complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735246A_ABST
    Figure CN119735246A_ABST
Patent Text Reader

Abstract

The present invention discloses a positive electrode material precursor and a preparation method thereof, a positive electrode material, and a secondary battery. The positive electrode material precursor provided by the present invention includes an internal annular doping layer, and the annular doping layer is doped with one or more metal ions. The positive electrode material precursor provided above forms a "transition zone" similar to a ring in the positive electrode material precursor by doping at an appropriate position, which clears the blockage in the lithium ion transmission process, increases the diffusion coefficient, and thus improves the electrochemical performance of the material end.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a positive electrode material precursor and a preparation method thereof, a positive electrode material and a secondary battery. Background Art

[0002] With the rapid development of the new energy field, lithium-ion batteries have broad application prospects due to their advantages such as high energy density, no memory effect, low self-discharge rate, good safety and environmental protection. Layered lithium nickel cobalt manganese oxygen cathode material, also known as ternary material or NCM, is one of the commonly used cathode materials in lithium-ion batteries. Compared with traditional cathode materials, it is better compatible with the advantages of lithium nickel oxide (LNO), lithium cobalt oxide (LCO) and lithium manganese oxide (LMO). The ternary synergistic effect enables it to have high capacity, stable cycle performance, relatively low cost, long life and other advantages. It has become one of the mainstream application materials in the lithium battery market. In order to meet the needs of the rapid development of the market, it is necessary to further improve the electrochemical properties of ternary cathode materials, among which element doping is one of the most commonly used modification strategies.

[0003] The electrochemical performance of ternary material batteries is mainly determined by the ternary precursors. Therefore, doping and preparing ternary precursors during the coprecipitation process can not only improve the electrochemical performance of ternary materials, but also has the advantages of lower doping cost and easier operation compared to doping in the ternary material preparation section, and is suitable for large-scale production. Studies have found that proper doping of ternary materials and their precursors can improve their electrochemical performance, while excessive or improper doping can easily change the crystal structure of the material, thereby reducing the electrochemical performance. In addition, the addition of doping elements during the reaction process increases the cost of the reaction, increases the risk of environmental pollution, and further increases the complexity of the synthesis process. The experimental results show that after adding doping elements to the stabilization process of the ternary precursor, it is easy to affect the growth rate of the reaction, which does not conform to the growth trend of the original stabilization process, so that the index morphology and structure of the ternary precursor do not meet the requirements.

[0004] Therefore, while ensuring the improvement of the electrical properties of ternary materials, controlling the cost of raw materials and not significantly increasing the difficulty of process synthesis are issues that need to be focused on in mass production. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above technical background and provide a positive electrode material precursor and a preparation method thereof, a positive electrode material and a secondary battery.

[0006] The present invention provides a positive electrode material precursor, which comprises an annular doping layer arranged along the circumferential direction, wherein one or more metal ions are doped in the annular doping layer.

[0007] The present invention also provides a preparation method of the positive electrode material precursor according to the above-mentioned method, which comprises: in the process of preparing the positive electrode material precursor by the coprecipitation method, the oxidant is continuously introduced in the early stage of the coprecipitation reaction to obtain the inner core, after the nucleation is completed, the pH in the reactor is lowered to allow the particles to continue to grow, when the particle size grows to 40%-80% of the target particle size, the introduction of the oxidant is reduced or stopped, and the dopant solution is pumped in under the protection of an inert gas, and after the annular doping layer of suitable thickness is grown, the pumping of the dopant solution is stopped, and the reaction is continued to grow the outer shell layer on the annular doping layer to prepare the positive electrode material precursor.

[0008] The present invention also provides a positive electrode material, which is obtained by mixing and sintering the positive electrode material precursor and a lithium source.

[0009] The present invention also provides a secondary battery, wherein the positive electrode of the secondary battery comprises the positive electrode material.

[0010] The present invention has the following beneficial effects.

[0011] The present invention provides a positive electrode material precursor and a preparation method thereof, a positive electrode material, and a secondary battery. The positive electrode material precursor provided by the present invention includes an annular doping layer arranged along the circumferential direction, and the annular doping layer is doped with one or more metal ions. A "transition zone" similar to an annular shape is formed in the positive electrode material precursor to clear the blockage in the lithium ion transmission process, increase the diffusion coefficient, and thus improve the electrochemical performance of the ternary material. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0013] Figure 1 Schematic diagram of the internal structure of the annular doped layer ternary cathode precursor;

[0014] Figure 2 The scanning electron microscope (left) and cross-sectional electron microscope diagram (right) of a small-particle ternary cathode precursor with a ring-shaped doping layer;

[0015] Figure 3 The scanning electron microscope image (left) and the cross-sectional electron microscope diagram (right) of the ternary cathode precursor with a ring-shaped doping layer and large particles;

[0016] Figure 4 CP-SEM image of the annular doped layer ternary cathode precursor;

[0017] Figure 5 The undoped and Zr-doped 4+ XRD curve of the ternary cathode precursor with a ring-shaped doped layer. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0019] A positive electrode material precursor and a preparation method thereof, a positive electrode material, and a secondary battery provided in an embodiment of the present invention are specifically described below.

[0020] In a first aspect, an embodiment of the present invention provides a positive electrode material precursor, wherein the positive electrode material precursor includes an annular doping layer arranged along a circumferential direction, wherein one or more metal ions are doped in the annular doping layer.

[0021] The more regular and dense structure in the positive electrode material can increase the mechanical strength, reduce the surface side reactions and improve the cycle performance. However, in the highly ordered and dense structure, the distance between particles is small, forming a narrow channel, which increases the migration resistance of lithium ions. The mixing of lithium ions and nickel ions will further cause the ion channel to be blocked, reducing the electrochemical performance of the material. In addition, the dense structure in the material will lead to strong interactions between particles, so that lithium ions need to overcome large electrostatic repulsion and mechanical resistance when crossing, which increases the difficulty of transmission and slows down the overall migration rate.

[0022] The embodiment of the present invention provides a positive electrode material precursor, which includes an annular doping layer arranged in a circumferential direction, and one or more metal ions are doped in the annular doping layer. The positive electrode material obtained by annularly doping the positive electrode material precursor provided by the embodiment of the present invention at an appropriate position allows the doping elements to occupy a specific position while ensuring that the morphology and structure remain basically unchanged, thereby reducing the blockage caused by the mixing of lithium ions and nickel ions. The lattice spacing enlarged by the doped ions allows lithium ions to migrate more smoothly in the material, playing the role of a transition zone, and more lithium ions are deintercalated from the material, thereby improving the electrochemical performance of the positive electrode material.

[0023] In some optional embodiments, the cathode material precursor includes a core, an annular doping layer and an outer shell layer from the inside to the outside;

[0024] Preferably, the inner core is a loose porous structure;

[0025] Preferably, the annular doping layer is one or more layers, and the multiple annular doping layers are distributed at intervals. More preferably, the interval distance is 2-5 μm;

[0026] Preferably, the outer shell layer includes a number of primary particles in the shape of rods, and the number of primary particles is radially arranged outside the annular doping layer.

[0027] In some alternative embodiments, the cathode material precursor includes a loose core, an annular doping layer, and a dense outer shell layer in sequence from the inside to the outside, and the specific form is as Figure 1-Figure 4 shown.

[0028] In some alternative embodiments, the chemical formula of the cathode material precursor is Ni x Co y Mn z M a (OH)2, where: 0.33 ≤ x ≤ 0.9, 0 < y ≤ 0.4, 0 < z ≤ 0.4, x + y + z = 1, the radius of the doping element M is close to the radius of one of the nickel element, cobalt element, and manganese element, and the value of a is mainly determined by the morphology structure and particle size of the precursor. It should be noted that the doping element M in the cathode material precursor can be one or more metal elements, which can be selected according to actual needs. Preferably, the radius of the doping element M is close to the radius of one of the nickel element, cobalt element, and manganese element, including: Nb 5+ 、W 6+ 、Ti 4+ 、Mg 2+ 、Zr 4 、Al 3+ One or several of them, which will be beneficial to the insertion and extraction of lithium ions, thereby improving the electrochemical performance at the cathode material end.

[0029] In the second aspect, the embodiment of the present invention provides a preparation method of the cathode material precursor according to the above, which includes: during the preparation of the cathode material precursor by the coprecipitation method, an oxidant is continuously introduced in the early stage of the coprecipitation reaction to obtain the core. After the nucleation is completed, the pH in the reaction kettle is reduced to allow the particles to continue growing. When the particle size grows to 40%-80% of the target particle size, the introduction of the oxidant is reduced or stopped. Under the protection of an inert gas, a doping agent solution is pumped in. After growing an appropriate thickness of the annular doping layer, the pumping of the doping agent solution is stopped, and the reaction is continued to grow the outer shell layer on the annular doping layer to obtain the cathode material precursor.

[0030] It is worth noting that in the preparation method of the above-mentioned positive electrode material precursor, an oxidant is continuously introduced in the early stage of the coprecipitation reaction to obtain an inner core with a loose porous structure. The relatively loose inner core can facilitate the deintercalation of lithium ions. After the nucleation is completed, the pH in the reactor is lowered to allow the particles to continue to grow. When the particle size grows to 40%-80% of the target particle size, the introduction of the oxidant is reduced or stopped, thereby reducing the degree of oxidation of the material in the reactor. Under the protection of an inert gas, a dopant solution (the dopant solution is one or more of the oxide, nitrate, and hydrochloride of the doping element M) is pumped in, and a ring-shaped doping layer of the desired thickness and the doping element can be grown on the surface of the loose porous inner core. After that, the pumping of the dopant solution is stopped, and the reaction is continued to grow an outer shell layer on the ring-shaped doping layer to prepare a positive electrode material precursor.

[0031] In the process of preparing the positive electrode material precursor, in order to ensure the cycle performance of the material, the material morphology and internal structure prepared are generally dense, the compaction density is high and the thickness of the primary particles is thick, but this structure is not conducive to the transmission of lithium ions and limits the capacity of the material. Doping in the ternary precursor can improve this situation, but it is easy to cause the growth rate of the precursor to change after doping, so that the index morphology and structure of the precursor do not meet the demand. Therefore, the embodiment of the present invention provides a method for preparing a positive electrode material precursor, and while keeping the precursor morphology structure and reaction process basically unchanged, an annular doping layer is added at a specific position during the reaction process, and the amount of doping is small. The reaction process of the positive electrode material precursor has little effect, so that when the original control process is basically unchanged, the reaction process caused by doping is avoided. Serious changes, thereby causing concentration, temperature, stirring speed, ammonia value, atmosphere, pH and other factors are redesigned and explored. While achieving the goal of controlling the cost of raw materials as much as possible, the electrochemical properties of the material, especially the capacity characteristics, are improved. The method is completed by physical adjustment and an appropriate amount of doping agent, and the operation method is simple, and it is suitable for doping of various series of positive electrode precursors.

[0032] In some alternative embodiments, the oxidizing agent is selected from hydrogen peroxide.

[0033] In some optional embodiments, pumping the dopant solution under the protection of an inert gas includes: pumping the dopant solution from the feed port of the reactor through an external device, the rotation speed of the external device matches the concentration of the dopant solution, and stopping pumping the dopant solution when the particle size or electron microscope changes by 0.1-0.3 μm.

[0034] In some optional embodiments, the method further includes: aging the slurry in the reactor after the reaction is completed, washing the aged slurry with hot alkali and hot pure water in sequence, drying after dehydration, and obtaining a positive electrode material precursor through mixing, screening, demagnetization and packaging.

[0035] As can be seen from the above, the embodiment of the invention provides a method for preparing the positive electrode material precursor according to the above, which adds an annular doping layer at a specific position in the reaction process while keeping the precursor morphology structure and reaction process basically unchanged, and does not require additional process treatment when introducing doping elements, and is suitable for the preparation of the entire series of NCM precursors. Compared with the conventional doping process, the above method provided by the embodiment of the present invention also has the following advantages: the dosage of the dopant is small, and it is pumped into the reactor through small equipment such as peristaltic pumps, which is fast and convenient to access and has a low application cost; it can be applied to precursors with different particle size requirements, and can be applied to multiple stages of precursors. There are no application taboos for the problem of lithium ion transmission obstruction, and it does not affect the original reaction, retains the results of the previous development, and reduces R&D investment; the introduction of doping ions in the production process of the positive electrode material precursor to form an annular doping layer greatly shortens the preparation cycle, improves production efficiency, and is conducive to large-scale production.

[0036] In a third aspect, an embodiment of the present invention provides a positive electrode material, which is obtained by mixing and sintering the above-mentioned positive electrode material precursor and a lithium source.

[0037] The embodiment of the present invention provides a positive electrode material, which is obtained by mixing and sintering the positive electrode material precursor and a lithium source. During the preparation process of the positive electrode material precursor provided by the embodiment of the present invention, the required doping ions are doped at specific positions, and the prepared positive electrode material precursor containing doping elements is directly used for subsequent sintering. Since a "transition zone" similar to a ring is formed in the positive electrode material precursor, the blockage in the lithium ion transmission process is cleared, the diffusion coefficient is increased, and the electrochemical performance of the positive electrode material is improved.

[0038] In some optional embodiments, the sintering temperature is 500-1200° C., and the calcination time is 10-30 h.

[0039] In a fourth aspect, an embodiment of the present invention provides a secondary battery, wherein a positive electrode of the secondary battery includes the positive electrode material described above.

[0040] The present invention will be further described below in conjunction with the embodiments.

[0041] Example 1

[0042] This example prepares Zr 4+ The ion ring doping layer precursor and the ternary positive electrode material include the following steps:

[0043] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese mixed salt solution is 7:1:2, the concentration of the nickel-cobalt-manganese mixed salt solution is 1.8 mol / L, the concentration of the hydrogen peroxide solution is 3 mol / L, and the concentration of the zirconium salt solution is 0.004 mol / L. The mass percentage concentration of the ammonia water is 16%, and the mass percentage concentration of the liquid alkali solution is 28%. The bottom liquid of the reactor is prepared at a temperature of 50°C, an ammonia value of 10 g / L, and a pH value of 12.0.

[0044] A nickel-cobalt-manganese mixed salt solution, ammonia water and liquid alkali are introduced into the reactor at the same time, and hydrogen peroxide solution is continuously introduced to oxidize the inner core. The stirring speed is set to 600 rpm, and the pH is gradually reduced after 5 hours until it remains unchanged after 15 hours. When the particle size grows to 2 μm, the introduction of hydrogen peroxide solution is stopped, and the peristaltic pump is started to introduce zirconium salt solution at a pump speed of 30 rpm. When the particle size grows to close to 2.2 μm, the peristaltic pump is turned off to continue the reaction until the physicochemical indicators are qualified and the feeding is suspended.

[0045] The reactor material is placed in an aging kettle for aging. After aging, it is washed and dehydrated, and then dried. After mixing, screening, demagnetization and packaging, Zr 4+ Annular doped layer ternary positive electrode precursor.

[0046] Zr 4+ The annular doping layer ternary positive electrode precursor and lithium carbonate are fully mixed in a molar ratio of 2:1 to obtain a mixture of the precursor and lithium carbonate. The mixture is placed in a high-temperature sintering furnace at 800°C for 24 hours in an air atmosphere, and the modified ternary positive electrode material is obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0047] Example 2

[0048] This example prepares Zr 4+ Ions and Al 3+ The annular doping layer precursor and the ternary positive electrode material include the following steps:

[0049] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese mixed salt solution is 6:2:2, the concentration of the nickel-cobalt-manganese mixed salt solution is 2.0moL / L, the concentration of the configured zirconium salt solution is 0.002moL / L, the concentration of the configured hydrogen peroxide solution is 3mol / L, and the concentration of the configured aluminum salt solution is 0.002moL / L. The mass percentage concentration of the configured ammonia water is 16%, and the mass percentage concentration of the liquid alkali solution is 28%. The bottom liquid of the reactor is configured with a temperature of 60°C, an ammonia value of 5g / L, and a pH value of 11.6.

[0050] A nickel-cobalt-manganese mixed salt solution, ammonia water and liquid alkali are introduced into the reactor at the same time, and hydrogen peroxide solution is continuously introduced to oxidize the inner core. The stirring speed is set to 750 rpm. After 8 hours, the pH is gradually reduced until it remains unchanged after 18 hours. When the particle size grows to 2.4 μm, the introduction of hydrogen peroxide solution is suspended, and the peristaltic pump is started to introduce zirconium salt solution and aluminum salt solution respectively at a pump speed of 25 rpm. When the particle size grows to close to 2.5 μm, the peristaltic pump is turned off to continue the reaction, and the feeding is suspended after the physicochemical indicators are qualified.

[0051] The reactor material is placed in an aging kettle for aging. After aging, it is washed and dehydrated, and then dried. After mixing, screening, demagnetization and packaging, Zr 4+ and Al 3+ Annular doped layer ternary positive electrode precursor.

[0052] Zr 4+ and Al 3+ The annular doping layer ternary positive electrode precursor and lithium carbonate are fully mixed in a molar ratio of 2:1 to obtain a mixture of the precursor and lithium carbonate. The mixture is placed in a high-temperature sintering furnace at 850°C for 20 hours in an air atmosphere, and the modified ternary positive electrode material is obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0053] Comparative Example 1

[0054] This embodiment prepares an undoped precursor and a ternary positive electrode material, comprising the following steps:

[0055] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese mixed salt solution is 7:1:2, the concentration of the nickel-cobalt-manganese mixed salt solution is 1.8 mol / L, and the concentration of the hydrogen peroxide solution is 3 mol / L. The mass percentage concentration of the ammonia water is 16%, and the mass percentage concentration of the liquid alkali solution is 28%. The bottom liquid of the reactor is prepared at a temperature of 50°C, an ammonia value of 10 g / L, and a pH value of 12.0.

[0056] A nickel-cobalt-manganese mixed salt solution, ammonia water and liquid alkali are introduced into the reactor at the same time, and a hydrogen peroxide solution is continuously introduced to oxidize the inner core. The stirring speed is set to 600 rpm. After 5 hours, the pH is gradually reduced until it remains unchanged after 15 hours. When the particle size grows to 2 μm, the introduction of hydrogen peroxide solution is stopped, and the feeding is suspended until the physical and chemical indicators are qualified.

[0057] The materials in the reactor are placed in an aging reactor for aging. After aging, they are washed and dehydrated, and then dried. After mixing, screening, demagnetization and packaging, an undoped ternary positive electrode precursor is obtained.

[0058] The undoped ternary cathode precursor and lithium carbonate were fully mixed in a molar ratio of 2:1 to obtain a mixture of the precursor and lithium carbonate. The mixture was placed in a high-temperature sintering furnace at 800°C for 24 hours under air atmosphere, and the modified ternary cathode material was obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0059] Comparative Example 2

[0060] This example prepares Zr 4+ Ion doping precursor and ternary cathode material, including the following steps:

[0061] The molar ratio of nickel, cobalt and manganese in the nickel-cobalt-manganese mixed salt solution is 7:1:2, the concentration of the nickel-cobalt-manganese mixed salt solution is 1.8 mol / L, the concentration of the hydrogen peroxide solution is 3 mol / L, and the concentration of the zirconium salt solution is 0.004 mol / L. The mass percentage concentration of the ammonia water is 16%, and the mass percentage concentration of the liquid alkali solution is 28%. The bottom liquid of the reactor is prepared at a temperature of 50°C, an ammonia value of 10 g / L, and a pH value of 12.0.

[0062] A nickel-cobalt-manganese mixed salt solution, a zirconium salt solution, ammonia water and liquid alkali are introduced into the reactor at the same time, and a hydrogen peroxide solution is continuously introduced to oxidize the inner core. The stirring speed is set to 600 rpm. After 5 hours, the pH is gradually reduced until it remains unchanged after 15 hours. When the particle size grows to 2 μm, the introduction of hydrogen peroxide solution is stopped. The particle size grows rapidly during the reaction. When the particle size grows to the required range, the feeding is suspended. The physical and chemical indicators such as tap density and specific surface area are quite different from those of the original process, and the morphology structure is looser.

[0063] The reactor material is placed in an aging kettle for aging. After aging, it is washed and dehydrated, and then dried. After mixing, screening, demagnetization and packaging, Zr 4+ Ion doping of ternary precursors.

[0064] Zr 4+ The ion-doped ternary precursor and lithium carbonate are fully mixed in a molar ratio of 2:1 to obtain a mixture of the precursor and lithium carbonate. The mixture is placed in a high-temperature sintering furnace at 800°C for 24 hours in an air atmosphere, and the modified ternary positive electrode material is obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0065] Comparative Example 3

[0066] This comparative example prepared Zr 4+ The ion ring doping layer precursor and the ternary positive electrode material include the following steps:

[0067] The nickel-cobalt-manganese mixed salt solution, ammonia water and liquid alkali are simultaneously introduced into the reactor, and the hydrogen peroxide solution is continuously introduced to oxidize the kernel, the stirring speed is set to 600rpm, and the pH is gradually reduced after 5h until it remains unchanged after 15h. When the particle size grows to 2μm, the hydrogen peroxide solution is stopped, and when the particle size grows to 3μm, the peristaltic pump is started to pass the zirconium salt solution at a pump speed of 30rpm, and the peristaltic pump is turned off when the particle size grows to close to 3.2μm to continue the reaction, until the particle size grows to 3.4μm and the feeding is suspended. The rest is reacted according to the same process parameters as in Example 1, and the modified ternary positive electrode material is obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0068] Comparative Example 4

[0069] This comparative example prepared Zr 4+ The ion ring doping layer precursor and the ternary positive electrode material include the following steps:

[0070] The nickel-cobalt-manganese mixed salt solution, ammonia water and liquid alkali are simultaneously introduced into the reactor, and the hydrogen peroxide solution is continuously introduced to oxidize the kernel, the stirring speed is set to 600 rpm, and the pH is gradually reduced after 5 hours until it remains unchanged after 15 hours. When the particle size grows to 2 μm, the hydrogen peroxide solution is stopped, and the peristaltic pump is started to pass the zirconium salt solution at a pump speed of 30 rpm. When the particle size grows to close to 2.05 μm, the peristaltic pump is turned off to continue the reaction until the physical and chemical indicators are qualified. The rest is reacted according to the same process parameters as in Example 1, and the modified ternary positive electrode material is obtained after natural cooling, crushing, screening, demagnetization and packaging.

[0071] The obtained ternary positive electrode material, conductive carbon, and polyvinylidene fluoride were used in a ratio of 93:3:4 to prepare a button half-cell, and a metal lithium sheet was used as the negative electrode. The test results of the ternary positive electrode materials prepared in the embodiment and the comparative example are shown in Table 1 below.

[0072] Table 1

[0073]

[0074] Combining the above table 1 and Figure 5 It can be seen that: the Zr 4+ The annular doped layer and the undoped ternary positive electrode precursor, namely Example 1 and Comparative Example 1, have XRD curves as shown in Figure 5 It can be seen that after the ring doping inside the precursor, its peak shape and peak intensity have no obvious change, and have no significant effect on the internal structure of the ternary precursor. Combined with the electrochemical performance data comparison table shown in Table 1, it can be seen that with Zr 4+ Compared with the undoped ternary precursor, the capacity performance of the ternary precursor of the ion ring doping layer is improved while keeping the cycle performance basically unchanged.

[0075] In Example 2, Zr is selected 4+ and Al 3+ Doping to prepare the annular doped layer ternary cathode precursor, the reaction process is similar to that of single Zr 4+ The doping process is similar.

[0076] In Comparative Example 2, compared with Comparative Example 1, it can be found that the reaction process and product indicators are changed when the method of the present invention is not used for full-process doping while keeping the process basically unchanged. If full-process doping is required, it is necessary to further adjust the control parameters for the reaction process, optimize or re-explore the control process, so as to meet product requirements.

[0077] In Comparative Example 3, compared with Example 1 and Comparative Example 1, the cycle performance is basically the same, and the capacity performance is between the two. Therefore, the position of the annular doping layer in the internal structure of the precursor plays an important role. It is inferred that when the outer shell layer is close to the edge, the obstruction of the lithium ion transmission channel is not obvious, and the annular doping layer added here fails to play a good role in clearing the ion transmission channel.

[0078] In Comparative Example 4, compared with Example 1 and Comparative Example 1, the cycle performance is basically the same, and the capacity performance is close to that of the undoped precursor. Therefore, the thickness of the annular doping layer of the ternary precursor also plays an important role. When the thickness of the doping layer is too thin, it fails to have a significant effect on the material properties; when the thickness of the doping layer is too thick (such as Comparative Example 2), it will affect the overall reaction process.

[0079] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A cathode material precursor, characterized in that: The positive electrode material precursor includes an annular doping layer arranged along the circumferential direction, and one or more metal ions are doped in the annular doping layer.

2. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor comprises a core, an annular doping layer and an outer shell layer from the inside to the outside; Preferably, the inner core is a loose porous structure; Preferably, the annular doping layer is one or more layers, and the multiple annular doping layers are spaced apart, and more preferably the spacing is 2-5 μm; Preferably, the outer shell layer comprises a plurality of primary particles with a rod-like structure, and the plurality of primary particles are radially arranged outside the annular doping layer.

3. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor comprises a loose inner core, an annular doping layer and a dense outer shell layer from the inside to the outside.

4. The cathode material precursor according to claim 1, characterized in that: The chemical formula of the cathode material precursor is Ni x Co y Mn z M a (OH)2, where: 0.33 ≤ x ≤ 0.9, 0 < y ≤ 0.4, 0 < z ≤ 0.4, x + y + z = 1, the radius of the doping element M is close to the radius of one of the nickel element, cobalt element, and manganese element, and the value of a is mainly determined by the morphology structure and particle size of the precursor.

5. A method for preparing a cathode material precursor according to any one of claims 1 to 4, characterized in that: The method comprises: in the process of preparing a positive electrode material precursor by a coprecipitation method, an oxidant is continuously introduced in the early stage of a coprecipitation reaction to obtain a core, after the nucleation is completed, the pH in the reactor is lowered to allow the particles to continue to grow, when the particle size grows to 40%-80% of the target particle size, the introduction of the oxidant is reduced or stopped, a dopant solution is pumped in under the protection of an inert gas, after an annular doping layer of suitable thickness is grown, the pumping of the dopant solution is stopped, the reaction is continued to grow an outer shell layer on the annular doping layer, and a positive electrode material precursor is prepared.

6. The preparation method according to claim 5, characterized in that: The oxidizing agent is selected from hydrogen peroxide.

7. The preparation method according to claim 5, characterized in that: Pumping the dopant solution under the protection of inert gas includes: pumping the dopant solution from the feed port of the reactor through an external device, the rotation speed of the external device matches the concentration of the dopant solution, and stopping pumping the dopant solution when the particle size or electron microscope changes by 0.1-0.3μm.

8. The preparation method according to claim 5, characterized in that: Also includes: The slurry in the reactor after the reaction is completed is aged, and the aged slurry is washed with hot alkali and hot pure water in turn, and then dried after dehydration. The positive electrode material precursor is obtained through mixing, screening, demagnetization and packaging.

9. A positive electrode material, characterized in that: The positive electrode material is obtained by mixing and sintering the positive electrode material precursor according to any one of claims 1 to 4 with a lithium source.

10. A secondary battery, characterized in that: The secondary battery positive electrode comprises the positive electrode material according to claim 9.